Geological interpretation of the wave field in Mesozoic and Cenozoic sedimentary complexes of the transition zone between the South Caspian and Middle Caspian Basins using seismostratigraphic analysis method - Namazli, Nurlan; Abdulla-zade, Murad (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Purpose. This study investigates the tectonic and sedimentary evolution of the transition zone between the South Caspian Basin and the Middle Caspian Basin. The research aims to analyze seismic stratigraphic sequences to improve understanding of the basin’s geological history, sedimentary processes, and hydrocarbon potential. It also seeks to clarify the structural features and tectonic mechanisms responsible for the formation and evolution of this complex geological region.Methodology. The study employs seismostratigraphy, focusing on seismic sequence and seismic facies analysis. Seismic data were analyzed to identify sedimentary structures, stratigraphic sequences, and tectonic features. The seismic sections oriented in northwest-southeast and northeast-southwest directions were divided into ten seismic stratigraphic sequences (SS-1 to SS-10). These sequences were studied to determine their depositional environments, tectonic settings, and reflection characteristics. Seismic facies analysis helped interpret depositional conditions and sedimentary dynamics within each sequence, contributing to identifying structural traps and hydrocarbon reservoirs.Results. Key Seismic Features: Features such as onlaps, toplaps, pinch-outs, clinoforms, and erosional truncations were identified, suggesting favorable conditions for hydrocarbon accumulation, particularly in SS-3 (Upper Cretaceous), SS-5 (Maikop Series), and SS-7 (Productive Series). Tectonic Evolution: The region's tectonic evolution includes subduction, rifting, and the platform development. These geodynamic processes controlled the sedimentation conditions and structural deformations. Seismic Reflection Patterns: Seismic reflections indicate significant variations in sedimentation rates and depositional environments. For example, Jurassic and Lower Cretaceous sequences (SS-1 and SS-2) show chaotic and discontinuous reflections, while Late Pliocene and Quaternary sequences (SS-8 and SS-10) have continuous, high-amplitude reflections, suggesting contrasting depositional conditions. Tectonic Influence: Evidence of syn-sedimentary tectonics, including fault-related deformation and subsidence-driven sedimentation, was observed, emphasizing tectonic activity's role in shaping the region’s stratigraphy and influencing hydrocarbon distribution.Scientific Novelty. The study offers new insights into the tectonic and sedimentary history of the transition zone of the South Caspian Basin and the Middle Caspian Basin. It refines existing theories regarding the basin's formation by integrating seismostratigraphy with geological interpretations. The research advances the understanding of subsurface structural complexities, highlighting the interaction of tectonic forces and sedimentary processes in shaping the region's geological framework.Practical Significance. The findings have significant implications for oil and gas exploration. Key geological structures such as pinch-out zones, onlap unconformities, and erosional truncations provide critical information for hydrocarbon exploration. Particularly, the Upper Cretaceous and Oligocene-Miocene sections show favorable conditions for non-anticlinal traps, suggesting promising exploration targets. The study also highlights the role of tectonic activity in reservoir formation and distribution, aiding future exploration and drilling efforts in the region.